A rose flavor compound activating the NRF2 pathway in dendritic cells ameliorates contact hypersensitivity in mice - Kodama, Naoki; Okada, Hikaru; Hachisu, Masakazu; Ando, Miki; Ito, Naoto; Nagata, Kazuki; Katagiri, Mayuka; Yasuda, Yayoi; Hiroki, Ikumi; Yashiro, Takuya; Ichihara, Gaku; Yamamoto, Masayuki; et al. (Frontiers in Nutrition, 2023)
Dendritic cells (DCs), which are typical antigen-presenting cells, localize to various sites in the body, particularly the front line of infection as sentinels, and are involved in innate and adaptive immune responses. Although the functions of DCs, such as pathogen-induced cytokine production and antigen-specific T cell activation, are important for host defenses against infection and tumorigenesis, the hyper- and/or extended activation of DCs leads to inflammatory and autoimmune diseases. In the present study, beta-damascone, a major ingredient of rose fragrance, was selected from an aroma library as a candidate compound that suppresses antigen-induced immune responses. Beta-damascone inhibited the functions of DCs, including the antigen-dependent proliferation of T cells, DC-induced Th1 development, and the TLR ligand-induced production of inflammatory cytokines by DCs. The beta-damascone treatment also increased the protein level of the transcription factor NRF2, which plays key roles in antioxidant responses, and the transcription of Hmox1, a target gene of NRF2, in DCs. Nrf2-/- DCs induced Th1-development and produced large amount of IL-12p40 even in the presence of beta-damascone, whereas these functions by Nrf2+/- DCs were inhibited by beta-damascone under the same conditions. The intake of beta-damascone suppressed ear swelling in contact hypersensitivity (CHS) model mice, but not in CHS-induced Nrf2-/- mice. Collectively, the present results indicate the potential of the rose aroma compound beta-damascone, which suppresses DC-mediated immune responses by activating the NRF2 pathway in DCs, for the prevention and/or attenuation of immune-mediated diseases